2020
DOI: 10.3389/fcimb.2020.00041
|View full text |Cite
|
Sign up to set email alerts
|

Tick-Borne Encephalitis Virus Infection Alters the Sialome of Ixodes ricinus Ticks During the Earliest Stages of Feeding

Abstract: Ticks are hematophagous arthropods that transmit a number of pathogens while feeding. Among these is tick-borne encephalitis virus (TBEV), a flavivirus transmitted by Ixodes ricinus ticks in the temperate zone of Europe. The infection results in febrile illness progressing to encephalitis and meningitis with a possibility of fatality or long-term neurological sequelae. The composition of tick saliva plays an essential role in the initial virus transmission during tick feeding. Ticks secrete a diverse range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 82 publications
0
13
0
2
Order By: Relevance
“…In animal studies, TBEV has been shown to cause changes in salivary gland transcription that change the manner in which the tick interacts with the host skin so as to support a more rapid infection. 77 This is a complimentary effect of the antiviral response within the salivary gland and acts in parallel, with the virus utilizing tick saliva and adjusting its composition to benefit its own transmission by coopting the tick's immune response. Generally, this manifests as increased production of tick immune-modulating compounds, possibly related to the tick's own immune response to the virus.…”
Section: Changes To the Salivary Composition Of Infected Ticksmentioning
confidence: 99%
“…In animal studies, TBEV has been shown to cause changes in salivary gland transcription that change the manner in which the tick interacts with the host skin so as to support a more rapid infection. 77 This is a complimentary effect of the antiviral response within the salivary gland and acts in parallel, with the virus utilizing tick saliva and adjusting its composition to benefit its own transmission by coopting the tick's immune response. Generally, this manifests as increased production of tick immune-modulating compounds, possibly related to the tick's own immune response to the virus.…”
Section: Changes To the Salivary Composition Of Infected Ticksmentioning
confidence: 99%
“…They then penetrate the hemocoel (the tick’s body cavity filled with hemolymph), thus reaching the salivary glands and from there entering the host [29]. The act of feeding itself leads to differential expression of several salivary components of ticks and this differential expression is further significantly altered when ticks are infected with tick borne encephalitis virus (TBEV, transmission of which is more rapid than that of B. burgdorferi ) [30]. Since this notion may be relevant to the transmission efficiency of the infection, it is another reason why it makes sense to remove ticks properly and as early as possible.…”
Section: Penetration Of the Skinmentioning
confidence: 99%
“…Sie dringen dann in das Hämocoel (die mit Hämolymphe gefüllte Leibeshöhle der Zecke) ein, gelangen so zu den Speicheldrüsen und von dort in den Wirt [29]. Der Saugakt selbst führt zu differenzieller Expression mehrerer Speichelkomponenten der Zecken und diese differenzielle Expression wird weiter signifikant verändert, wenn Zecken mit dem Frühsommer‐Meningoenzephalitis‐Virus ( tick borne encephalitis virus [TBEV], dessen Übertragung schneller als die von B. burgdorferi erfolgt) infiziert sind [30]. Da dieser Aspekt möglicherweise für die Übertragungseffizienz der Infektion relevant ist, ist es auch deshalb sinnvoll, Zecken so früh wie möglich sachgerecht zu entfernen.…”
Section: Penetration Der Hautunclassified
“…Zu den mindestens 27 Gruppen der Peptid-und Protein-Speichelbestandteile der Ixodidae gehören verschiedene Mitglieder der Lipocalin-, Kunitz-Domänen-, Cystatin-, Basic Tail-, Ixostatin-und Metalloprotease-Familien [42]. Außerdem kann sich die Zusammensetzung durch Besiedlung mit Pathogenen deutlich ändern [30,32,[43][44][45] und es scheint sogar eine erhebliche interindividuelle Variabilität unter Zecken einer einzigen Spezies zu existieren, wie dies bei Ixodes ricinus demonstriert wurde [46]. Zecken produzieren möglicherweise den komplexesten Speichel aller Tiere [47].…”
Section: Nahrungsaufnahme Und Speichelsekretionunclassified